2009
DOI: 10.1179/174328809x405973
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectricity and microcurrent therapy for tissue healing – a narrative review

Abstract: Background: Microcurrent therapy (MCT) uses electric currents similar to those produced by the body during tissue healing. It may be a particularly beneficial where endogenous healing has failed. Aim: To review evidence regarding microcurrent in tissue healing and the application of MCT. Methods: All peer-reviewed studies concerning microcurrent and MCT were sought, and representative literature was synthesised to indicate the scope and weight of current evidence.Results: Microcurrent appears to play a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 135 publications
2
53
0
4
Order By: Relevance
“…24 Our results suggest that, by decreasing the dry matter content and increasing the water content of the injured tissue, electrical ions could circulate into the injured area faster than in normal tissue. 38 Our histologic results confirmed the above results, and demonstrated that, although inflammation is increased by the presence of the prostheses, the inflammatory cells declined after the inflammatory phase of tendon healing, and no marked inflammation was seen during fibroplasia and remodeling stages of tendon healing in the treated lesions. Severe and prolonged inflammatory reaction is not beneficial in tendon healing.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…24 Our results suggest that, by decreasing the dry matter content and increasing the water content of the injured tissue, electrical ions could circulate into the injured area faster than in normal tissue. 38 Our histologic results confirmed the above results, and demonstrated that, although inflammation is increased by the presence of the prostheses, the inflammatory cells declined after the inflammatory phase of tendon healing, and no marked inflammation was seen during fibroplasia and remodeling stages of tendon healing in the treated lesions. Severe and prolonged inflammatory reaction is not beneficial in tendon healing.…”
Section: Discussionsupporting
confidence: 78%
“…[45][46][47] When a tissue is damaged, its bioelectrical characteristics change, so that the electrical currents diminish as healing progresses, and the normal values is reestablished once healing is completed. 38,47 A major role of the collagen implant and its covering PDS sheath was to conduct the migrated fibroblasts in the longitudinal axis of the implant; we clarified this as a tenoconductive characteristic. This longitudinal axis was along the normal anatomical direction of the tendon-muscle unit.…”
Section: 44mentioning
confidence: 99%
“…Thus, according to results of the present study and those of our previous study, sensory ES, via an increase in expression of FGF-2 during the early phase of healing, may induce upregulation of VEGF during the proliferation phase of the healing process. The reason why sensory ES was more effective in the release of FGF-2 at the wound site is yet unclear, but may be related to the ability of microamperage ES to mimic the natural electrical field, or current, created following injury that facilitates the migration of cells toward the wound site [40][41]. The fibroblasts, endothelial cells, and macrophages, as predominant producers of FGF-2 at the wound site [7,[28][29], migrate toward the cathode [9,34].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that microcurrents increased wound contraction. Poltawski and Watson 13) reported that endogenous fields are intrinsic to a number of metabolic processes, including development, adaptation and repair. In addition, it is known that electrical stimulation fosters division and transfer of fibroblasts and keratinocytes, increases DNA and protein synthesis ability leading to wound healing 17) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that microcurrents influence tissue changes in the process of wound healing 9,10,13) . This study conducted digital image analyses and quantitative sensory tests to examine the effects of microcurrents on temporal tissue reactions such as the inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%